2020
DOI: 10.3390/ijerph17207637
|View full text |Cite
|
Sign up to set email alerts
|

Urban vs. Rural Socioeconomic Differences in the Nutritional Quality of Household Packaged Food Purchases by Store Type

Abstract: The U.S. food system is rapidly changing, including the growth of mass merchandisers and dollar stores, which may impact the quality of packaged food purchases (PFPs). Furthermore, diet-related disparities exist by socioeconomic status (SES) and rural residence. We use data from the 2010–2018 Nielsen Homescan Panel to describe the nutritional profiles of PFPs by store type and to assess whether these vary by household urbanicity and SES. Store types include grocery stores, mass merchandisers, club stores, onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In accordance, the Helsinki Health Study survey found that the difference in the consumption of fresh vegetables and fish, increased in favor of people with a higher education level, between 2000–2002 and 2007 [ 36 ]. Outside of Europe, disparities by income and educational level also widened for the purchases of fruits, vegetables and the percentage of calories from sugar between 2008 and 2018 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, the Helsinki Health Study survey found that the difference in the consumption of fresh vegetables and fish, increased in favor of people with a higher education level, between 2000–2002 and 2007 [ 36 ]. Outside of Europe, disparities by income and educational level also widened for the purchases of fruits, vegetables and the percentage of calories from sugar between 2008 and 2018 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of other ongoing work using large, national data sets on household purchases and nutritional label data at the barcode level, 31 , 32 we were also able to categorize every purchased item as a nonfood item (eg, toilet paper, magazine, or tobacco) or a food item. Among food items, we further examined 3 specific categories as being particularly relevant for health outcomes (eTable 1 in the Supplement ): (1) fruits, vegetables, legumes, and nuts; (2) less healthy foods including processed meats and processed seafood, desserts, sweet snacks, salty snacks, candy, chocolate, gum, sweeteners, and toppings; and (3) sugar-sweetened beverages.…”
Section: Methodsmentioning
confidence: 99%
“…This Special Issue includes research designed to better understand consumer food shopping patterns, particularly across understudied populations. Original research by Lacko and colleagues [8] updates and extends prior work examining trends in grocery sales since 2012. The authors document the top sources of calories across different retail store types, break this down by urban or rural household residence and household income, and then examine the interaction between household income and urbanicity.…”
Section: Consumer Food Shopping Patternsmentioning
confidence: 89%